2024
DOI: 10.1530/etj-23-0130
|View full text |Cite
|
Sign up to set email alerts
|

Association of sensitivity to thyroid hormones with all-cause mortality in euthyroid US adults: a nationwide cohort study

Genfeng Yu,
Siyang Liu,
Cheng Song
et al.

Abstract: Background This study aimed to examine the associations of thyroid hormone sensitivity indices, including free triiodothyronine to free thyroxine (FT3/FT4) ratio, thyroid feedback quantile-based index by FT4 (TFQIFT4), thyroid-stimulating hormone index (TSHI), and thyrotrophic thyroxine resistance index (TT4RI) with all-cause mortality in euthyroid adults. Methods The study included 6243 euthyroid adults from the National Health and Nutrition Examination Survey (NHANES) 2007–2012. FT3/FT4 ratio, TFQIFT4, TSHI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Inversamente, uma coorte retrospectiva demonstrou que maior relação T3L/T4L estava ligada à diminuição da mortalidade por todas as causas e cardiovascular 31 . Outro estudo longitudinal que avaliou mortalidade global em adultos eutireoidianos identificou uma associação em forma de U com razão T3L/T4L 33 . Em grupos de indivíduos mais idosos, as concentrações de T3r estão associadas a uma função física inferior 5 .…”
Section: Discussionunclassified
“…Inversamente, uma coorte retrospectiva demonstrou que maior relação T3L/T4L estava ligada à diminuição da mortalidade por todas as causas e cardiovascular 31 . Outro estudo longitudinal que avaliou mortalidade global em adultos eutireoidianos identificou uma associação em forma de U com razão T3L/T4L 33 . Em grupos de indivíduos mais idosos, as concentrações de T3r estão associadas a uma função física inferior 5 .…”
Section: Discussionunclassified
“…Conversely, a retrospective cohort demonstrated that a higher FT3/FT4 ratio was linked to decreased all-cause and cardiovascular mortality 31 . Another longitudinal study that evaluated overall mortality in euthyroid adults identified a U-shaped association with the FT3/FT4 ratio 33 . In groups of older individuals, rT3 concentrations are associated with lower physical function 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The value of TFQI is between -1 and 1. A lower value indicates higher thyroid hormone sensitivity (12,19).…”
Section: Definitions Of Tfqimentioning
confidence: 99%